Double genetic disruption of lactate dehydrogenases A and B is required to ablate the “Warburg effect” restricting tumor growth to oxidative metabolism - Zdralevic, Masa; Brand, Almut; Di Ianni, Lorenza; Dettmer, Katja; Reinders, Joerg; Singer, Katrin; Peter, Katrin; Schnell, Annette; Bruss, Christina; Decking, Sonja-Maria; Koehl, Gudrun; Felipe-Abrio, Blanca; et al. (Journal of Biological Chemistry, 2018)
Increased glucose consumption distinguishes cancer cells from normal cells and is known as the “Warburg effect” because of increased glycolysis. Lactate dehydrogenase A (LDHA) is a key glycolytic enzyme, a hallmark of aggressive cancers, and believed to be the major enzyme responsible for pyruvate-to-lactate conversion. To elucidate its role in tumor growth, we disrupted both the LDHA and LDHB genes in two cancer cell lines (human colon adenocarcinoma and murine melanoma cells). Surprisingly, neither LDHA nor LDHB knockout strongly reduced lactate secretion. In contrast, double knockout (LDHA/ B-DKO) fully suppressed LDH activity and lactate secretion. Furthermore, under normoxia, LDHA/B-DKO cells survived the genetic block by shifting their metabolism to oxidative phosphorylation (OXPHOS), entailing a 2-fold reduction in proliferation rates in vitro and in vivo compared with their WT counterparts. Under hypoxia (1% oxygen), however, LDHA/B suppression completely abolished in vitro growth, consistent with the reliance on OXPHOS. Interestingly, activation of the respiratory capacity operated by the LDHA/B-DKO genetic block as well as the resilient growth were not consequences of long-term adaptation. They could be reproduced pharmacolog-ically by treating WT cells with an LDHA/B-specific inhibitor (GNE-140). These findings demonstrate that the Warburg effect is not only based on high LDHA expression, as both LDHA and LDHB need to be deleted to suppress fermentative glycolysis. Finally, we demonstrate that the Warburg effect is dispensable even in aggressive tumors and that the metabolic shift to OXPHOS caused by LDHA/B genetic disruptions is responsible for the tumors’ escape and growth.
CRIS-Team Scopus Importer:2023-03-23